Investigating the Role of Emotional Intelligence for Improving English Speaking Skills at the University Level - Mahmood; Zahid Ali Jatoi; Dr. Syed Hyder Raza Shah (Research Journal of Psychology, 2025)
This research aims to assess the degree of emotional intelligence on English-speaking skills among university-level students of Sanghar. About the study, as a quantitative research study, it looks at the impact of emotional intelligence on students’ levels of confidence, anxiety, and assertiveness while participating in English-speaking activities. Questionnaires were completed by 84 students from the English Department of Shaheed Benazir Bhutto University, Sanghar Campus, using a simple random sampling method. Concerning the speaking experience in the classroom and self-emotion terms, the following statements were used in the questionnaire. Descriptive statistics, specifically mean scores, indicated that students who possess higher emotional intelligence were more confident, motivated, and willing to speak in class than those with a comparatively lower level of emotional intelligence. Self-reporting in the positive affective domain included affirming statements in assertion to practice, including “I like making dialogues,” where the mean score was 3.58, and “When I practice, I can develop myself,” where the mean score was 3.62 out of 5. In role-play, there was a moderate level of anxiety detected, which points towards the need to consider creating conducive learning environments. These results have underlined the need for educators to incorporate emotional supportive features like multisensory and error-friendly approaches in their language acquisition practice. Lastly, the study finds that EI is positively related to improvement in speaking skills; thus, it should be incorporated in teaching and learning processes when developing curriculum for second language acquisition.